New Evidence for Ag-Sputtered Materials Inactivating Bacteria by Surface Contact without the Release of Ag Ions: End of a Long Controversy? - Rtimi, Sami; Konstantinidis, Stephanos; Britun, Nikolay; Nadtochenko, Victor; Khmel, Inessa; Kiwi, John (ACS applied materials & interfaces, 2020)
The study provides new evidence for Ag-coated polyester (PES) mediating inactivation by way of genetically engineered (without porins, from now denoted porinless bacteria). This allows the quantification of the bactericidal kinetics induced by the Ag surface without the intervention of Ag ions. Bacterial inactivation mediated by Ag-PES was seen to be completed within 60 min. The samples were prepared by high-power impulse magnetron sputtering (HiPIMS) at different sputter powers. In anaerobic media, this process required 120 min. The amounts of ions (Ar , Ag , and Ag ) generated during the deposition by direct current magnetron sputtering (DCMS) and HiPIMS were determined by mass spectrometry. The thickness of the Ag films sputtered on PES by DCMS (0.28 A) during 100 s was found to be 340 nm. Thicknesses of 250, 230, and 200 nm were found when sputtering with HiPIMS was tuned at 8, 17, and 30 A, respectively. By scanning transmission electron microscopy (STEM-HAADF), the atomic distribution of Ag and oxygen was detected. By X-ray photoelectron spectroscopy (XPS), a shift in the Ag oxidation state was observed within the bacterial inactivation period. This reveals redox catalysis within the time required for the total bacterial inactivation due to the interaction between the bacterial suspension and Ag-PES. Surface properties of the Ag-coated PES samples were additionally investigated by X-ray diffraction (XRD). The formation of Ag plasmon was detected by diffuse reflectance spectroscopy (DRS) and was a function of the applied sputtering energy. The indoor sunlight irradiation dose required to induce an accelerated bacterial inactivation was found to be 5-10 mW/cm .